Implementasi Manajemen Berbasis Sekolah dalam Meningkatkan Mutu Pendidikan di MTs NW Montong Baan - Elwin; M. Siratul Khaeri (Indonesian Journal of Action Research, 2025)
Purpose – This study aims to analyze the implementation of School-Based Management (SBM) in improving educational quality at MTs NW Montong Baan. The study focuses on the implementation process, the role of the principal, and the supporting and inhibiting factors affecting SBM implementation. Design/methods – This research employed a qualitative approach with a descriptive design. Data were collected through observation, in-depth interviews, and documentation involving the principal, educational staff, and community members. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. Findings – The results reveal that SBM implementation was carried out through six main components, namely curriculum management, educational personnel management, student management, financial management, facilities and infrastructure management, and school-community relations. The study found that SBM implementation contributed to improved student achievement, community-based curriculum development, and increased parental participation in school activities. Supporting factors included principal leadership, community support, and government assistance. Meanwhile, limited facilities and infrastructure became the main obstacles, although these challenges were minimized through participatory and adaptive management.